Multi objective optimization of surface roughness and workpiece surface temperature in turning operation - Nooraziah A.; Tiagrajah V.J. (Trans Tech Publications Ltd, 2023)
This paper presents the optimization of multiple performance characteristics (surface roughness and workpiece surface temperature) based on the Taguchi method. Three controllable factors of the turning process were studied at three levels. The single objective optimization was conducted using Taguchi method. The multiple Signal-to-Noise (MSNR) value was used to correspond to multi objective cases. The optimum combination of cutting parameters was obtained based on the highest value of MSNR. © (2014) Trans Tech Publications, Switzerland.